Imperfect Aspect in English and Indonesian Verbs - Prastianto, Hendro R (Universitas Nusantara PGRI Kediri, 2015)
Abstract: This paper explores the imperfect aspect in English and Indonesian Verbs. The aim is to compare and analyze the use of this aspect, which frequently appears in various English texts for junior and senior high school students in the current Indonesian curriculum. The result of this study shows that this aspect serves as the background of an activity and it requires morphological and lexical problems in English but lexical problem in Indonesian. In addition, this exploration is useful for building up the learning materials for such courses as lexical semantics and advanced grammar. Key words: imperfect, aspect, verbs Abstrak: Tulisan ini menyelidiki aspek imperfek kata kerja Bahasa Inggris dan Indonesia. Tujuannya membanding dan menganalisis penggunaan aspek ini, yang sering muncul dalam aneka ragam teks berbahasa Inggris untuk siswa SMP dan SMA di kurikulum Indonesia. Hasil kajian menunjukkan fungsi aspek sebagai latar belakang aktivtas dan membutuhkan pelibatan masalah morfologi dan leksikal dalam bahasa Inggris dan masalah leksikal dalam bahasa Indonesia. Selain itu, kajian ini bermanfaat untuk menyediakan materi pembelajaran perkuliahan semantik leksikal dan tata bahasa lanjut.